НЕКОТОРЫЕ ТЕКСТОВЫЕ АКТУАЛИЗАТОРЫ И ИХ МЕТАТЕКСТОВЫЕ И МЕЖЛИЧНОСТНЫЕ РОЛИ (Philological Studies, 2019)
Our analysis of recorded narrative texts is centred upon eight textual «actualizers» with various textual and interpersonal functions. Special attention is given to those functions through which the interpersonal relations between the discourse participants are revealed, i.e. to those interpersonal functions by means of which the speaker «helps» the receiver overcome the temporal and spatial distance from the textual world under construction and with which the speaker expresses his / her expectations about the receiver's being familiar with what is being talked about (i.e. his / her expectations about their having a shared universe of discourse). It is worth emphasizing that each of the actualizers dealt with performs different textual and interpersonal functions, which are interconnected and which complement one another. If one fails to take into consideration a single one out of their numerous functions, any further study of the functional realizations of the actualizers described is made impossible.